Cuidado centrado na pessoa: tradução e validação de ferramentas de manejo e acompanhamento de pacientes com queixa de zumbido - Miranda, Amanda Câmara (2020)
Tinnitus is a conscious auditory perception of sound in the absence of an external sound source. In view of the negative interference that this can cause in the patient's life, professionals' sensitivity to meet the needs of the individual in a broad way is necessary, and not just stick to the disease. Currently, care based on Person-Centered Care (CCP) has been used, aiming to help initial contact, providing better professional-patient communication. The CCP works on the psychosocial aspects of tinnitus, promoting health care designed around the patient's needs, desires and perspectives through empathy, counseling, open listening and a good professional health-patient relationship. The Ida Institute, a Danish institution, has developed some tools to assist in this process, however, these have been little used so far, thus requiring the translation and validation of these in other languages so that professionals from different countries can use them in their clinical practice and, thus, work may emerge that proves the effectiveness of this care. Therefore, this study aimed to: 1) translate and adapt the tinnitus tools of the IDA Institute to Brazilian Portuguese and 2) validate the use of the tools in clinical practice. The translation and adaptation of the material provided by Ida Institute into Brazilian Portuguese was carried out through the following steps: translation, proofreading, equivalence (semantic, idiomatic, experimental and conceptual), final version. In the second part of the study, to validate the material, calls were made using the tools and strategies of the CCP. The consultations were videotaped and subsequently evaluated by analyzing the speech therapist's speech, in order to observe the use of CCP in patients with tinnitus in clinical practice. It can be concluded that the translation and adaptation of the material into Brazilian Portuguese was well conducted and executed. In addition, it was observed that, after validating and analyzing the professional's discourse using the translated material, it points out effective elements and with CCP mechanisms that can be used by other professionals in clinical practice, in favor of the quality of care provided by tinnitus patients.